Quality of Health Care Activity in Educational Institutions: Conceptual Aspect - N. V. Tretyakova; V. A. Fedorov (Russian State Vocational Pedagogical University, 2015)
The paper deals with one of the priority tasks of Russian educational system - developing the health responsibility. The recent health deterioration trend among children and adolescents calls for the complex health care measures, equally affecting the learning outcomes. The authors argue that there is a need for proper definition and specification of the key term of health care quality. However, the analysis of the available scientific and documentary recourses demonstrates the absence of such unified definition. The authors describe the existing approaches to defining the health care quality, and examine structural components of the health care activity, their interrelations and interdependence. In authors' opinion, the synthesis of the available research materials provides the basis for further studies in the theory and practice of quality management activities regarding the health protection of children, adolescents and young adults in educational institutions.